When pride still mattered : a life of Vince Lombardi - Maraniss, David. frey50 (New York, NY : Simon & Schuster, 1999)
This book "is the quintessential story of the American family: how Vince Lombardi, the son of an immigrant Italian butcher, rose to the top, and how his character and will to prevail transformed him, his wife, his children, his players, his sport, and ultimately the entire country. It is also a vibrant football story as well as a study of national myths and an absorbing account of "mythmakers"--Dust jacket.
Tattoos -- Fordham Road -- We Do, or Die -- Saints -- Lost in the Bronx -- Fields of Friendly Strife -- Blaik's Boys -- No Substitute for Victory -- Cult of the New -- This Pride of Giants -- The Foreigner -- Packer Sweep -- Trinity -- Remembering Jack -- Golden -- A Night at the Elks -- Daylight -- The End of Something -- Foot of the Cross -- Coming in Second -- Winning Isn't Everything -- It's the Only Thing -- In Search of Meaning -- Ice -- Until Lombardi Loves You -- The Empty Room -- Taking Charge in Washington -- Run to Win.
Keywords: Lombardi, Vince; Green Bay Packers (Football team) -- History; Football coaches -- United States; American football -- USA; Biography & autobiography: sport -- USA